(untitled) (Revista de Diavulgación L’esprit Ingénieux, 2024)
Water as a natural resource is important for all living being on earth. But, due to the lack of awareness and disrespect for water resources, contamination of the sources has occurred, generating diseases and alterations in human health and the living beings that drink on them. At present, there are several technological advances that allow water potabilization processes to be carried out. The identification of unconventional processes is key to their proper implementation and define which of these processes helps in the stabilization of water quality parameters. A survey on the area of study was conducted, and water samples were taken to specify the values ​​of water quality parameters that influence the processes that can be implemented at the source of the Caimán and Peña Amarilla generate water purification for the community of Vereda del Pantano de Vargas in the city of Paipa (Boyacá).